2019
DOI: 10.3390/ijerph16173063
|View full text |Cite
|
Sign up to set email alerts
|

Romantic Attraction and Substance Use in 15-Year-Old Adolescents from Eight European Countries

Abstract: Sexual minority youth are at higher risk of substance use than heterosexual youth. However, most evidence in this area is from North America, and it is unclear whether the findings can be generalized to other cultures and countries. In this investigation, we used data from the 2014 Health Behaviour in School-aged Children (HBSC) study to compare substance use in same- and both-gender attracted 15-year-old adolescents from eight European countries (n = 14,545) to that of their peers who reported opposite-gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 66 publications
4
17
0
Order By: Relevance
“…This result echoes earlier findings that adolescents who identify as bisexual face disproportionate health risks across a wide range of determinants and health outcomes compared to their peers who identify as heterosexual, or even lesbian or gay [73][74][75]. Our international HBSC team found that among adolescents from eight European countries or regions, both-gender attracted youth were the most likely to report substance use [76] or rate their health as poor and report multiple health symptoms [77]. This pattern of unfavorable outcomes for both-gender attracted or bisexual youth may be because bisexuality is often "invisible" or denied by members of the individuals' social network.…”
Section: Better Outcomes Brighter Futures In Sexual Minority Adolescents: Discrimination Resilience and Social Agencysupporting
confidence: 85%
“…This result echoes earlier findings that adolescents who identify as bisexual face disproportionate health risks across a wide range of determinants and health outcomes compared to their peers who identify as heterosexual, or even lesbian or gay [73][74][75]. Our international HBSC team found that among adolescents from eight European countries or regions, both-gender attracted youth were the most likely to report substance use [76] or rate their health as poor and report multiple health symptoms [77]. This pattern of unfavorable outcomes for both-gender attracted or bisexual youth may be because bisexuality is often "invisible" or denied by members of the individuals' social network.…”
Section: Better Outcomes Brighter Futures In Sexual Minority Adolescents: Discrimination Resilience and Social Agencysupporting
confidence: 85%
“…While most North American studies have reported similar gender differences, this finding is at odds with previous evidence from Belgium (DeSmet et al, 2018). Recent findings demonstrate that opposite-and both-gender love is associated with disproportionate risk of substance use (Költő et al, 2019) and elevated rates of psychosomatic health symptoms and poor self-rated health (Költő et al, 2020) among adolescents in Europe. Together, these findings suggest that elevated rates of bullying victimization among sexual minority adolescents, and its negative health correlates, may be widespread across different countries and cultures.…”
Section: Bullying Victimization In Sexual Minority Youth: Is It Unive...mentioning
confidence: 74%
“…lesbian) and plurisexual (e.g. pansexual, reporting attraction to more than one gender) individuals [25][26][27][28]. The variation in PPU prevalence may stem from real differences between cultural, gender-and sexual orientation-related groups [29].…”
Section: Introductionmentioning
confidence: 99%